Experiences of Medical Team on Perceived Social Support during Covid-19 Pandemic :A Qualitative Study - Farshadfar, Sareh; Hatefi, Masoud; Meisami, Amir Hosein; Borji, Milad (The journal of contemporary issues in business and government, 2021)
Background:COVID-19 disease is a new disease that is very important how Informing the patient about it. This study was conducted with the aim of investigating the experiences of the nurses’ staff on how to inform the patient to get infected with COVID-19. Methods:Twelve health care providers (8 nurses and 4 anesthesiologists) in a educational and medical center in the city of Ilam in From February to June 2020participated in the study with purposeful sampling. Semi-structured interviews were used to collect data, and the study began with the open question,"Describe your experience of identifying the disease in patientswith COVID-19". To analyze the data, the conventional qualitative content analysiswas performed. Results: Participants in this study included 12 medical personnel, of which 7 (58.4%) were male and 5 (41.6%) were female. Based on the findings, 2 main themes and 7 sub-themes were extracted. The main themes extracted from this study include A) Passing the patient of the purgatory ofCOVID-19 diagnosis including four sub-themes: 1) Waiting for a diagnosis, 2) Announcing stepbystep the diagnosis, 3) giving information, 4) acceptance or resistance; B) Entering the important others to the purgatory of COVID-19 diagnosisincluding three sub-themes: 1)Entering the key family members, 2) Entering the physician, 3) Entering the relatives working as medical staff. Conclusion:Diagnosing the disease of COVID-19 is like a purgatory for patient and staff. To help the patient get through this purgatory, important others are introduced by the staff. Eventually the patient either accepts the disease or resists accepting it.